2021
DOI: 10.1097/nmd.0000000000001432
|View full text |Cite
|
Sign up to set email alerts
|

Treating Avoidant Personality Disorder With Combined Individual Metacognitive Interpersonal Therapy and Group Mentalization-Based Treatment

Abstract: Avoidant personality disorder (AvPD) is a severe but understudied condition. The current pilot project reports data on acceptability and outcomes of a novel treatment combining biweekly individual metacognitive interpersonal therapy (MIT) and weekly mentalization-based therapy (MBT) group therapy. A total of 30 patients with AvPD were consecutively included in the program. The primary outcome was AvPD-specific personality functioning measured by selfreport after treatment. Secondary outcomes were symptom distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 97 publications
2
20
0
Order By: Relevance
“…A meta‐analysis on 15 treatment effectiveness studies has shown that cognitive‐behavioural and psychodynamic approaches (along with social skills training) were beneficial for Cluster‐C PDs, although contradictory results were found and uncertainty remains regarding the relative effectiveness for DPD, APD and OCPD (Simon, 2009). More recent studies exploring new approaches show promising results but point to difficulty comparing established to newer treatments due to differing methodologies (Simonsen et al, 2022). Moreover, studies are often underpowered, focused solely on APD or did not study differences between PDs (Popolo et al, 2022; Simonsen et al, 2022; Skewes et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta‐analysis on 15 treatment effectiveness studies has shown that cognitive‐behavioural and psychodynamic approaches (along with social skills training) were beneficial for Cluster‐C PDs, although contradictory results were found and uncertainty remains regarding the relative effectiveness for DPD, APD and OCPD (Simon, 2009). More recent studies exploring new approaches show promising results but point to difficulty comparing established to newer treatments due to differing methodologies (Simonsen et al, 2022). Moreover, studies are often underpowered, focused solely on APD or did not study differences between PDs (Popolo et al, 2022; Simonsen et al, 2022; Skewes et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies exploring new approaches show promising results but point to difficulty comparing established to newer treatments due to differing methodologies (Simonsen et al, 2022). Moreover, studies are often underpowered, focused solely on APD or did not study differences between PDs (Popolo et al, 2022; Simonsen et al, 2022; Skewes et al, 2015). Regarding the differences between the Cluster‐C PDs in treatment effectiveness, previous studies are inconclusive; one study found that OCPD patients improved most (Barber et al, 1997), while other studies favoured APD patients (Karterud et al, 2003) or DPD patients (Seivewright et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Improvement of symptom distress in the present study seems better than demonstrated for patients with AvPD in a former study of traditional group-based psychodynamic treatments ( 10 , 124 ). Although research and treatment developments targeting this patient group are in progress ( 125 127 ), studies on AvPD features are still underrepresented ( 128 ). Our study specifically points to the pattern of prevailing restricted social engagement which may require more tailored intervention.…”
Section: Discussionmentioning
confidence: 99%
“…There is, however still a scarcity of treatment research focusing on AvPD ( 27 ). Only four randomized controlled trials (RCT) with a small number of patients have focused particularly on AvPD ( 28 31 ), and some additional natural design studies ( 32 35 ). A few RCTs have been conducted on cluster C personality disorders which have included more than 60% patients with AvPD ( 36 , 37 ).…”
Section: Introductionmentioning
confidence: 99%